Taxation of the use of Russian water resources - Bocharova, Irina; Rymanov, Alexander (Tecnología y ciencias del agua, 2022)
The article examines the taxation of the use of Russian water resources for various types of water use. The use of water resources can be regulated in different jurisdictions in different ways. While the objectives of different authorities may be the same (e.g., to encourage the most efficient use of water resources), the means to achieve these goals may vary. The use of the new form of compulsory payment (in the form of water tax) practically did not change the methodology for justifying the size of rates compared with the previous compulsory payment – payment for the use of water bodies. The water tax occupies an insignificant share of the revenues of the Russian consolidated budget. The reduced rate of water tax when taking water for supplying the population leads to a significant decrease (by 77-82 %, depending on the year) of the tax burden for this type of water use. An increased (five times) rate is applied when water is taken over the limit established for a specific water user, an increased (five times) rate is applied. The weight of the water tax, charged in 2006-2019 at an increased rate, varied in the range of 2-10 %.